Di Antara Kelindan Migrasi, Penguasaan Lahan dan Siasat Bertahan: Solidaritas Semu Kehidupan Petani di Perdesaan Jawa - Setiadi Setiadi (Sodality: Jurnal Sosiologi Pedesaan, 2021)
As the smallest social entity with its local forms of socio-cultural relations, each of Indonesia’s hamlet communities today is faced with the complexity of the dynamics of internal relationships. Sodality, believed to be the spirit of these relationships, is facing internal and external pressures. Limited access to resources, behavioral influences from out-migration, institutional changes, and the reinforced individualization of control over local resources make up such pressures. This study reveals the patterns of pseudo-solidarity that serves as a new spirit for the basis of relationships of hamlet residents. Pseudo-solidarity has become a strategy for community survival due to limited access to and control over sources of livelihood, changes in population structure that resulted from migration, and external pressures in the form of changes in socio-economic institutions. It serves as a compromise between maintaining harmony and playing out tactics to fulfill individual interests. Hamlet community members develop strategies and increase their negotiation abilities to meet their economic, social, and cultural needs. Taking advantage of the flexible, pretentious side of social relationships, they also raise their tolerance threshold towards the dynamics of life that are detrimental to them. This condition significantly weakens the solidarity within hamlet communities. This study used an anthropological approach to its data collection. Some of its methods include mini-surveys, observations, and in-depth interviews. Through kinship and biographical tracings, the study tracked the different processes of intergenerational mobility and migrations concerning, among others, land tenure and ownership of other resources.